(untitled) (BEOIBERÍSTICA - Revista de Estudios Ibéricos, Latinoamericanos y Comparativos (ISSN: 2560-4163 Online), 2021)
In this paper we present the Cervantine activity of the Serbian literary historian and comparatist Milan Marković. Marković developed his work during the 1930s. He authored a Cervantes’ biography and four articles published in reviews.